Gérer les risques liés au travail durant la grossesse. Vers un nouveau modèle de gestion de la santé et sécurité des travailleuses enceintes - Anne-Renée Gravel; Romaine Malenfant (Perspectives Interdisciplinaires sur le Travail et la Santé)
The workforce shortage problem in Quebec’s hospitals requires that the re-assignment rights of pregnant workers be respected when reconsidering work organization. The right to re-assignment provides an opportunity to question and improve – with the participation of the involved parties – the efficiency of approaches and methods regarding health and safety, production, and staff management. A new model is emerging as a result. Beginning with results from research carried out in hospitals from three Quebec regions, this paper shows how adding a prevention agent who is in charge of applying re-assignment rights makes it possible to effectively influence ergonomic and organizational constraints and to keep women working during pregnancy with a constructive approach that is beneficial for both workers and employers.